2018
DOI: 10.1177/0739456x18789251
|View full text |Cite
|
Sign up to set email alerts
|

What Shapes Uneven Access to Urban Amenities? Thick Injustice and the Legacy of Racial Discrimination in Denver’s Parks

Abstract: Like other urban amenities, parks are unevenly distributed throughout cities, with advantaged groups enjoying better access to better parks than more disadvantaged residents. Although such inequities are well documented, we know less about the mechanisms that shape them. We conduct a case study in Denver that includes a GIS analysis and interviews with local planners and historians. We find that while park funding systems have tended to steer investments into richer neighborhoods, racially discriminatory land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 43 publications
1
38
0
1
Order By: Relevance
“…In Rigolon's review of articles focusing on Global North cities, which is predominantly based on articles centering on the United States, 61% of the sampled studies analyzed racial-ethnic differences in access to green spaces [42], compared to only 13% in this review. This difference suggests that race and ethnicity might not be as relevant to describe disadvantage in the Global South as they are in the United States, where the long history of racial discrimination has led to today's inequities in access to green space [43,118]. Similarly, a few authors of studies on South Africa attributed the observed inequities in green space provision to the legacy of apartheid policies, which, until the early 1990s, enforced the segregation of White and Black individuals [77,89,96].…”
Section: Discussionmentioning
confidence: 99%
“…In Rigolon's review of articles focusing on Global North cities, which is predominantly based on articles centering on the United States, 61% of the sampled studies analyzed racial-ethnic differences in access to green spaces [42], compared to only 13% in this review. This difference suggests that race and ethnicity might not be as relevant to describe disadvantage in the Global South as they are in the United States, where the long history of racial discrimination has led to today's inequities in access to green space [43,118]. Similarly, a few authors of studies on South Africa attributed the observed inequities in green space provision to the legacy of apartheid policies, which, until the early 1990s, enforced the segregation of White and Black individuals [77,89,96].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite their value to central and city governments, critiques suggest that the fixed nature of metrics may actually limit their utility. It has also been suggested that cataloguing amenities or setting a 10-minute metric for the distance to the nearest green space fails to acknowledge variations in street hierarchies, personal mobility, site functionality (and its utility to users), the amenity value of a site or the wider spatial context of GI within an urban area [ 82 ]. As a consequence, although standardized metrics remain useful tools for policy-makers to assess provision, they are contested in terms of how effectively they shape delivery and whether they are appropriate mechanisms to meet the health, well-being and recreational needs of a given community.…”
Section: Distribution Of Green Infrastructure In Urban Areasmentioning
confidence: 99%
“…For instance, unevenly distributed greenspaces might aggravate the health inequity in cities, via unequal accessibility to greenspace resources, 5 and could be linked to racial discrimination and policies that privilege economic growth over equity. [37][38][39] Alternatively, linear-shaped parks could increase accessibility compared with parks with compact shapes. 40 And large parks might provide additional benefits when compared with small parks, by providing alternative recreational options.…”
Section: Discussionmentioning
confidence: 99%